Kebijakan Strategis Abu Bakar Ash-Shiddiq Pada Masa Khalifah Rasyidah - Purwanto, Ari (Civiliza Publishing, Indonesia., 2024)
The Caliph is the supreme leader of the Muslim community and is also the leader of the Islamic State, commonly known as Khalifatul Muslim. The election of Abu Bakr as caliph was not a mistake, but it was the best decision taken by the friends of the Prophet Muhammad SAW. Using library research methods, researchers search for, study, and understand literature related to Caliph Abu Bakar. The author focuses on the literature on the strategic policies taken by Caliph Abu Bakar As-Sidiq. This research shows that Abu Bakar As-Sidiq's strategic policy during the time of the Rasyidah Caliph was not to fight domestic rebels, territorial expansion, and the influence of Islamic states starting from the Roman and Persian to Iraqi territories. At this time, Baitul Mal and Judicial Institutions are also a priority. What is no less important is the policy of Caliph Abu Bakar As-Sidiq in collecting the Koran into one Mushaf.